Skin Fibroblasts from Patients with Type 1 Diabetes (T1D) Can Be Chemically Transdifferentiated into Insulin-Expressing Clusters: A Transgene-Free Approach - Pereyra Bonnet, Federico Alberto (2014)
The conversion of differentiated cells into insulin-producing cells is a promising approach for the autologous replacement of pancreatic cells in patients with type 1 diabetes (T1D). At present, cellular reprogramming strategies encompass ethical problems, epigenetic failure or teratoma formation, which has prompted the development of new approaches. Here, we report a novel technique for the conversion of skin fibroblasts from T1D patients into insulin-expressing clusters using only drug-based induction. Our results demonstrate that skin fibroblasts from diabetic patients have pancreatic differentiation capacities and avoid the necessity of using transgenic strategies, stem cell sources or global demethylation steps. These findings open new possibilities for studying diabetes mechanisms, drug screenings and ultimately autologous transgenic-free regenerative medicine therapies in patients with T1D.